2016
DOI: 10.1186/s12974-016-0711-7
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Schwann cell plasticity in chronic inflammatory demyelinating polyneuropathy (CIDP)

Abstract: BackgroundChronic inflammatory demyelinating polyneuropathy (CIDP) is often associated with chronic disability, which can be accounted to incomplete regeneration of injured axons. We hypothesized that Schwann cell support for regenerating axons may be altered in CIDP, which may account for the poor clinical recovery seen in many patients.MethodsWe exposed human and rodent Schwann cells to sera from CIDP patients and controls. In a model of chronic nerve denervation, we transplanted these conditioned Schwann ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 42 publications
0
20
0
1
Order By: Relevance
“…Therefore, neuroprotection and regeneration should be a further goal in the development of new treatment options in CIDP. Recently, it has been demonstrated that Schwann cells cultured with sera from CIDP patients support regenerating axons less effectively than Schwann cells conditioned with control sera due to a lower expression of granulocyte‐macrophage colony‐stimulating factor and other neurotrophins [16]. Furthermore, intrathecally applied steroids seem to have a protective role against oxidative stress in Schwann cells [17].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, neuroprotection and regeneration should be a further goal in the development of new treatment options in CIDP. Recently, it has been demonstrated that Schwann cells cultured with sera from CIDP patients support regenerating axons less effectively than Schwann cells conditioned with control sera due to a lower expression of granulocyte‐macrophage colony‐stimulating factor and other neurotrophins [16]. Furthermore, intrathecally applied steroids seem to have a protective role against oxidative stress in Schwann cells [17].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that CIDP patients show a diminished pro-regenerative function of Schwann cells leading to the axonal loss and therefore incomplete clinical recovery after treatment which is probably caused by inflammatory mediators [ 25 ]. Thus, differences in immune responses between typical and atypical CIDP we have demonstrated might also influence Schwann cell function resulting in different treatment responses and long-term outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of nerve regeneration is approximately 1 mm/day, depending on the site of the lesion and on the patient age. SC plasticity diminishes with age, showing an altered expression of c-Jun [111] and a weak regenerative capacity [112,113].…”
Section: Therapeutical Approaches Based On Schwann Cell Plasticitymentioning
confidence: 99%